Current trends in electron beam and laser powder bed fusion additive manufacturing of copper alloys: Composition, defects, properties, and challenges - Bhaskaranand Bhatt; Alessandra Martucci; Sara Biamino; Daniele Ugues; Federica Bondioli; Laura Montanaro; Mariangela Lombardi; Paolo Fino (Materials & Design)
Currently, laser and electron beam powder bed fusion (L/E-PBF) are prevalent in metal additive manufacturing (AM), demonstrating exceptional potential for producing copper (Cu) alloy components indispensable for numerous aerospace, automotive, energy, and marine applications. However, despite groundbreaking advances in metal AM, Cu alloys remain underdeveloped. This comprehensive review highlights the unremitting efforts to develop superior and bespoke L/E-PBF Cu alloy parts. Initially, roadblocks to Cu alloy printability are identified, along with solutions to surmount them, followed by feedstock development in the context of L/E-PBF. An extensive process-induced defect analysis is presented to assess the impact of powder feedstock characteristics, process parameters, and heat treatments. Furthermore, the mechanical, electrical, corrosion, and tribological properties of L/E-PBF-fabricated Cu alloy parts are elaborated to elucidate the nexus among material-microstructure-performance. In addition, this review delves into various strengthening mechanisms, the significance of post-processing heat treatment in stabilising non-equilibrium microstructures, and its influence on the material-property space. The discussion then extends to the importance of modelling for comprehending complex melt pool dynamics. Finally, the review uncovers lacunas and presents critical future research aspects to boost the technological readiness of L/E-PBF Cu alloys/composites for accelerated adoption.